A CMOS Micro-power, Class-AB “Flipped” Voltage Follower using the quasi floating-gate technique (2017)
This paper presents the design and characterization of a new analog voltage follower for low-voltage applications. The main idea is based on the “Flipped” Voltage Follower and the use of the quasi-floating gate technique for achieving class AB operation. A test cell was simulated and fabricated using a 0,5 μm CMOS technology. When the proposed circuit is supplied with VDD = 1,5 V, it presents a power consumption of only 413 μW. Measurement and experimental results show a gain bandwidth product of 10 MHz and a total harmonic distortion of 1,12 % at 1 MHz.